Advances in Iranian linguistics - Larson, Richard K.; Moradi, Sedigheh; Samiian, Vida (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2020)
"This volume brings together selected papers from the first North American Conference in Iranian Linguistics, which was organized by the linguistics department at Stony Brook University. Papers were selected to illustrate the range of frameworks, diverse areas of research and how the boundaries of linguistic analysis of Iranian languages have expanded over the years. The contributions collected in this volume address advancing research and complex methodological explorations in a broad range of topics in Persian syntax, morphology, phonology, semantics, typology and classification, as well as historical linguistics. Some of the papers also investigate less-studied and endangered Iranian languages such as Tat, Gilaki and Mazandarani, Sorani and Kurmanji Kurdish, and Zazaki. The volume will be of value to scholars in theoretical frameworks as well as those with typological and diachronic perspectives, and in particular to those working in Iranian linguistics"--